Disminución de ingresos por efectos de la morosidad en los créditos otorgados por la Cooperativa de Ahorro y Crédito San José Ltda., del cantón Montalvo, periodo 2020 - Galeas Peralta, Kerly Maribel (2021)
In this paper, the results obtained from the financial indicators are presented with the purpose of evaluating the situation and the economic performance of the San José Ltda. Montalvo Agency Savings and Credit Cooperative. The objective of this study is to analyze the delinquency that the loan portfolio presents; and the risk of running out of liquidity that the institution has. Liquidity focuses on the ability of the company to meet its obligations both in the short and long term. This research work has a qualitative approach, because it describes the observed and quantitative events, when analyzing the financial statements.